Biologically Structured Water (BSW) - A Review (Part 1): Structured Water (SW) Properties, BSW and Redox Biology, BSW and Bioenergetics - Ramsey, Craig L. (Journal of Basic & Applied Sciences, 2023)
A review of biologically structured water (BSW) is needed to support a more convincing argument of the significance of organized water to the overall health of living organisms. Research phrases related to BSW water are energized, hexagonal, interfacial, or bound water because they refer to biological water with similar structural, functionality, and general water properties. Structured water is formed by shortening hydrogen bonds (H-bonds) in free water, forming various polymeric water structures. In living organisms, BSW water has liquid crystalline properties that have excellent redox qualities due to the energized state of the hexagonal ring structure. Each hexagonal ring has a vortex of delocalized electrons and protons that form pi orbitals above and below each ring, contributing to myriad redox reactions within cells. In addition, the energized hexagonal water rings can be readily split or ionized with minimal energy inputs, providing the oxygen-based ions needed to initiate water respiration. The water respiration pathway can convert the high-grade chemical energy stored in energized, biologically structured water into supplemental energy for cells. The water respiration theory based on interfacial structured water is revisited due to recent findings of superconductivity water properties. The contribution of energized BSW water to redox biology and water respiration can be associated with improved metabolic efficiency and enhanced physiological performance in all life forms. Finally, this article will review recent findings involving quantum biology and BSW water. When BSW water is confined in extremely small sites such as proton wires or water wires, the water properties take on strange quantum properties that stretch the accepted theories of chemistry and physics.